Writing and constructing the self in Great Britain in the long eighteenth century - Baker, John; Leclair, Marion; Ingram, Allan (Seventeenth- and eighteenth-century studies., 2019)
The injunction, 'Know thyself!', resounding down the centuries, has never lost its appeal and urgency. The 'self' remains an abiding and universal concern, something at once intimate, indispensable and elusive; something we take for granted and yet remains difficult to pin down, describe or define. This volume of twelve essays explores how writers in different domains - philosophers and thinkers, novelists, poets, churchmen, political writers and others - construed, fashioned and expressed the self in written form in Great Britain in the course of the long eighteenth century from the Restoration to the period of the French Revolution. The essays are preceded by an introduction that seeks to frame several key aspects of the debate on the self in a succinct and open-minded spirit. The volume foregrounds the coming into being of a recognisably modern self.